Entomopathogenic Fungi as Alternatives to Chemical Acaricides: Challenges, Opportunities and Prospects for Sustainable Tick Control - Mahvish Rajput; Muhammad Sohail Sajid; Nasir Ahmed Rajput; David Robert George; Muhammad Usman; Muhammad Zeeshan; Owais Iqbal; Bachal Bhutto; Muhammad Atiq; Hafiz Muhammad Rizwan; Ian Kirimi Daniel; Olivier Andre Sparagano (Insects, 2024)
Entomopathogenic fungi (EPFs) can infect and kill a diverse range of arthropods, including ticks (Acari: Ixodidae) that can transmit various diseases to animals and humans. Consequently, the use of EPFs as a biocontrol method for managing tick populations has been explored as an alternative to chemical acaricides, which may have harmful effects on the environment and non-target species. This review summarizes studies conducted on EPFs for tick control between 1998 and 2024, identifying 9 different EPF species that have been used against 15 different species of ticks. One of the most well-known and widely researched EPFs used against ticks is Metarhizium anisopliae, a fungus known for its ability to infect and kill various arthropods. When applied to tick-infested areas, M. anisopliae spores attach to the tick’s cuticle, germinate, and penetrate through the cuticle, leading to the eventual death of the tick due to the fungal infection. Whilst a number of studies support the potential of this and other EPF species against ticks, this review suggests that limitations to their effective use may include factors such as heat, humidity, and ultraviolet light (UV-A and UV-B). This comprehensive review aims to provide an overview of the literature on the potential of EPFs in tick control, focusing on their mode of action, previous field successes/failures, advantages, potential applications, and prospects for future practical developments.